PROPAGANDA AGAMA DAN ANCAMAN TERHADAP TOLERANSI BERAGAMA (STUDI HADIS KARIKATUR NABI) - Nafriandi, Nafriandi (Turast: Jurnal Penelitian dan Pengabdian, 2013)
This study wants to see the threat which caused by religious propaganda against religious tolerance. Propagandahas two forms, the first is white propaganda which is to encourage others to support the own policy or plan.Second is black propaganda which directs others to think, behave, and act in different side. White propagandais essentially no different from advertising or promotion. While the black propaganda is to deliver informationin which is inserted partially or without loading the correct facts at all with the intent to convey an idea orsituation that does not exist. The freedom of expression in Denmark on the form of drawing cartoons of theProphet Muhammad can be assumed as an intentional insults to the Prophet and infuriated Muslims. Agroup of people in Denmark is likely insensitive and deliberately provoke Muslim anger to seek popularity. Forthe Danish society, freedom of the press are rights and interests should not be defeated by anything, includingreligion. This article explores the study of Hadith of the Prophet shape visualizing action in the context ofpropaganda and religious tolerance.